2023
DOI: 10.3390/medicina59010121
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Role of Electrical Stimulation in Osteoporosis: A Narrative Review

Abstract: Osteoporosis is mainly a geriatric disease with a high incidence, and the resulting spinal fractures and hip fractures cause great harm to patients. Anti-osteoporosis drugs are the main treatment for osteoporosis currently, but these drugs have potential clinical limitations and side effects, so the development of new therapies is of great significance to patients with osteoporosis. Electrical stimulation therapy mainly includes pulsed electromagnetic fields (PEMF), direct current (DC), and capacitive coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 76 publications
0
4
0
1
Order By: Relevance
“…The use of PEMFs is the treatment method with the greatest evidence of success. However, the specific treatment parameters of frequency and treatment time are not yet conclusive [65].…”
Section: Osteopenia and Osteoporosismentioning
confidence: 99%
“…The use of PEMFs is the treatment method with the greatest evidence of success. However, the specific treatment parameters of frequency and treatment time are not yet conclusive [65].…”
Section: Osteopenia and Osteoporosismentioning
confidence: 99%
“…Another review on electrical stimulation in osteoporosis locates clinical evidence that PEMFs may alleviate osteoporosis-related pain [49], and that bone mass and, thus, osteoporosis could be favorably influenced by PEMF through a RANKL/OPG and Wnt/-catenin pathway. Although the FDA has not yet approved PEMF for the treatment of osteoporosis, based on the current experimental and clinical data, this non-invasive procedure could be an effective adjunct in this indication.…”
Section: Osteopeniamentioning
confidence: 99%
“…As one of the most common orthopedic diseases, osteoporosis is mainly caused by bone resorption by osteoclasts being greater than bone formation by osteoblasts, resulting in a state of low bone mass, impaired bone tissue microstructure, increased bone fragility, and susceptibility to fracture. Numerous studies have shown that physical electrical stimulation, such as direct current, pulsed current, electric field, and electromagnetic field, can promote bone formation of osteoblasts [28,29], thus providing a certain alleviation and therapeutic effect on osteoporosis, and treatment through electrical stimulation has become a popular research topic.…”
Section: Wound Healing Osteoblast Proliferation and Differentiationmentioning
confidence: 99%